Case report: A severe case of generalized tetanus in a young cat - Zilli, Jessica; Häußler, Thomas C.; Ives, Edward J.; Schmidt, Martin J. (Frontiers in Veterinary Science, 2023)
A 10-month-old, 3kg, female spayed Domestic Shorthair cat was presented with a chronic, infected wound at the level of the proximo-lateral left pelvic limb. General physical examination revealed a weight-bearing lameness of the left pelvic limb, which was moderately and circumferentially swollen and edematous proximal to the tarsal joint. On the lateral aspect of the proximal thigh, there was a chronic wound of 1 cm in diameter and an additional exudative skin lesion was present throughout the whole length of the caudo-lateral thigh. Complete blood count and serum biochemistry profile revealed mild anemia, increased serum amyloid A, hyponatraemia, hypochloraemia, hypocalcaemia, hyperkalaemia, hypermagnesaemia, hyperglycaemia, increased creatine kinase and increased liver parameters. Surgical exploration of the wound was performed, and necrotizing fasciitis was suspected. The affected limb was amputated and swabs for bacterial culture were taken from both the skin lesions and surgical site before wound closure. One day after surgery, mild muscular contractions on the forehead and an increased muscle tone of the right pelvic limb were evident. One day later, the cat developed a generalized increase in extensor tone, with intermittent opisthotonos, resulting in lateral recumbency. Based on these clinical signs, a diagnosis of generalized tetanus was made and treatment with midazolam, methocarbamol and metronidazole was started. Despite an improvement of all blood parameters, the cat progressively deteriorated and four days after surgery, it developed episodes of tetanic convulsions, associated with hyperthermia and ventricular arrhythmias. Despite intensive care and medical management, the cat died following a cardio-respiratory arrest three days later. This case report describes a rare case of severe generalized tetanus in a young cat.